The problem of information security within the Russian political process - Ekaterina Miкhailovna GuginaNatalya Rinatovna Balynskaya, Tamara Nikolaevna Lukina,; Valeriya Vladimirovna Vikulina, Yuliya Leonidovna Kiva-Khamzina, Zoya Sergeevna Akmanova,; Vladimirovich Dremov, Vladimir (Opción, 2019)
The article discusses the possible operative levels, as well as traces that very level, wherein the public image is becoming an artificial credo, formed specifically for the target audience. The research uses a functional approach. As a result, there are certain ethical requirements that subjects of political interactions should strictly observe for their own security reasons. In conclusion, the observance of the norms of political ethics largely laid the foundation for both a normal and full-fledged dialogue and information security of the political activity of each subject and the entire Russian political process.